2005
DOI: 10.1038/nrc1753
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic PI3K deregulates transcription and translation

Abstract: There have long been indications of a role for PI3K (phosphatidylinositol 3-kinase) in cancer pathogenesis. Experimental data document a requirement for deregulation of both transcription and translation in PI3K-mediated oncogenic transformation. The recent discoveries of cancer-specific mutations in PIK3CA, the gene that encodes the catalytic subunit p110alpha of PI3K, have heightened the interest in the oncogenic potential of this lipid kinase and have made p110alpha an ideal drug target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
595
1
12

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 709 publications
(619 citation statements)
references
References 163 publications
11
595
1
12
Order By: Relevance
“…It has been shown that p110b possesses both lipid and protein kinase activities (reviewed in Bader et al, 2005;Engelman et al, 2006). To determine which activity of p110b kinase is involved in AR transactivation, we tested the effect of different p110b mutants, a total kinase-dead mutant (K805R) and a protein kinase only mutant (PKO, lipid kinase deficient) on Figure 1 Phosphoinositide 3-OH kinases (PI3K) p85a and p110b isoforms are essential for androgen-induced androgen receptor (AR) transactivation and cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that p110b possesses both lipid and protein kinase activities (reviewed in Bader et al, 2005;Engelman et al, 2006). To determine which activity of p110b kinase is involved in AR transactivation, we tested the effect of different p110b mutants, a total kinase-dead mutant (K805R) and a protein kinase only mutant (PKO, lipid kinase deficient) on Figure 1 Phosphoinositide 3-OH kinases (PI3K) p85a and p110b isoforms are essential for androgen-induced androgen receptor (AR) transactivation and cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Phosphoinositide 3-OH kinases (PI3Ks) regulate multiple cellular signal pathways (reviewed in Bader et al, 2005;Engelman et al, 2006). In mammalian cells, there are three classes (I, II and III) of PI3K isoforms, and the class I PI3Ks are further divided into two subtypes (IA p110 a/b/d and IB p110g), of which IA catalytic isoforms are associated with p85 regulatory subfamily, while IB p110g is associated with p101/p84 regulatory subunit.…”
Section: Introductionmentioning
confidence: 99%
“…The phosphatidylinositol 3-kinase (PI3K)/AKT signaling pathway is activated in multiple cancers, leading to oncogenic transformation (Vivanco and Sawyers, 2002;Bader et al, 2005;Wymann and Marone, 2005). Activation may result from activating mutations in PI3-kinase genes or inactivating mutations in the tumor suppressor gene PTEN (phosphatase and tensin homolog).…”
Section: Introductionmentioning
confidence: 99%
“…2,6 The RAS-MAPK and PI3K-AKT pathways are strongly interconnected and have a central role in tumorigenesis. RAS is activated by growth factors and hormone signaling, binding to RAF proteins (also named MAPKKKs).…”
mentioning
confidence: 99%